A denitration catalyst and a method for preparing the same

CN122875262APending Publication Date: 2026-10-09CHINA HUADIAN ENG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610805299.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本申请提供一种脱硝催化剂及其制备方法,旨在解决现有脱硝催化剂低温活性不足、抗硫抗水性差,易生成铵盐堵塞设备、成本高、副产物处理难等问题

Benefits of technology

[0017]本申请的有益效果包括:本申请所述脱硝催化剂适合工业化批量生产、低温活性性能优异、结构稳定抗高温抗老化、分散性佳活性位点充足、抗中毒能力强适合电厂烟气富含碱金属颗粒物和硫化物场景、机械强度高可塑性强且耐磨、成本经济固废资源化利用、传质效率高兼顾吸附与催化反应、表面纳米膜可阻挡水汽侵蚀活性位点,整体骨架为疏水稳定结构,避免水汽造成颗粒松散、活性组分流失,高湿工况下性能不衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application belongs to the technical field of air pollution control, and particularly relates to a denitration catalyst and a preparation method thereof. The denitration catalyst comprises the following raw materials in parts by weight: activated carbon 10-15 parts, manganese dioxide 22-25 parts, amino acid 12-15 parts, phosphoric acid 3-8 parts, phosphorite 2-5 parts, aluminum oxide 5-8 parts, clay mineral 10-15 parts and plastic fiber 8-12 parts. The beneficial effects of the application include that the denitration catalyst is suitable for industrialized batch production, has excellent low-temperature activity performance, is stable in structure and resistant to high temperature and aging, has good dispersibility, sufficient active sites, strong anti-poisoning capacity, is suitable for the scene where flue gas of power plants is rich in alkali metal particles and sulfides, has high mechanical strength, strong plasticity and wear resistance, is cost-effective, realizes resource utilization of solid waste, has high mass transfer efficiency, gives consideration to adsorption and catalytic reaction, the surface nano-membrane can block water vapor erosion of active sites, the overall skeleton is a hydrophobic stable structure, water vapor is prevented from causing particles to be loose and active components to be lost, and the performance is not attenuated under high-humidity working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of air pollution control technology, specifically relating to a denitrification catalyst and its preparation method. Background Technology

[0002] Low concentration NO in domestic thermal power plants x Treatment still relies on SCR and SNCR flue gas denitrification technologies, both of which use ammonia as a reducing agent. Their core limitation is the high-temperature reaction window, making them unsuitable for low-temperature, low-concentration flue gas conditions. Traditional processes require temperatures above 300℃ for stable operation, especially in NO2 environments. x Concentration 50mg / m 3 Under low-load conditions, denitrification efficiency decreases significantly; forcibly increasing efficiency can easily lead to excessive ammonia injection, causing ammonia escape exceeding standards. Gas turbine units have been required to [implement NOx measures]. x Emissions strictly controlled to 15 mg / m³ 3 The following points demonstrate that conventional high-temperature SCR alone cannot reliably achieve ultra-low emissions. While new technologies such as adsorption and biological denitrification are suitable for low-temperature scenarios and offer cost advantages, their denitrification efficiency, operational stability, and engineering maturity are insufficient, making it difficult to replace existing processes on a large scale. Therefore, it is evident that low-concentration NO under low-temperature conditions... x High-efficiency denitrification has become a prominent technical challenge in the industry, and improving existing denitrification processes has become an urgent direction for current research and engineering applications.

[0003] Existing low-temperature denitrification solutions mainly include low-temperature SCR, combined SNCR-SCR, activated carbon adsorption, biological denitrification, and oxidative absorption denitrification. Low-temperature SCR, relying on modified catalysts, can achieve efficient denitrification in the medium and low temperature range, but it generally suffers from weak sulfur and water resistance, easy formation of ammonium salts for clogging, and a significant risk of ammonia escape under low-concentration nitrogen oxide conditions. The combined SNCR-SCR process can reduce the reaction temperature and catalyst dosage, but the system coupling control is complex. Activated carbon adsorption has good low-temperature adaptability and can synergistically treat multiple pollutants, but it has shortcomings such as limited adsorption capacity, frequent regeneration, and high operation and maintenance costs. Biological denitrification can operate at room temperature and is inexpensive, but it has a slow reaction rate, poor resistance to operating condition fluctuations, and insufficient maturity for large-scale application. Oxidative absorption denitrification is not limited by temperature and is suitable for low-temperature flue gas, but it consumes a lot of oxidant, has high operating costs, and complicated by-product treatment. Although various low-temperature technologies can adapt to low-temperature and low-concentration conditions, they each have shortcomings in efficiency, stability, economy, or engineering application. There is no mature solution that can completely replace traditional high-temperature denitrification processes. Summary of the Invention

[0004] This application provides a denitrification catalyst and its preparation method, aiming to solve the problems of insufficient low-temperature activity, poor sulfur and water resistance, easy formation of ammonium salts to clog equipment, high cost, and difficulty in handling by-products of existing denitrification catalysts.

[0005] The first aspect of this application provides a denitrification catalyst comprising the following raw materials in parts by weight: 10-15 parts activated carbon, 22-25 parts manganese dioxide, 12-15 parts amino acids, 3-8 parts phosphoric acid, 2-5 parts phosphogypsum, 5-8 parts alumina, 10-15 parts clay minerals, and 8-12 parts plastic fibers.

[0006] According to some embodiments of the denitrification catalyst described in this application, the activated carbon includes one or more of coconut shell activated carbon, wood powder activated carbon, coal-based activated carbon, and bamboo-based activated carbon.

[0007] According to some embodiments of the denitrification catalyst described in this application, the plastic fiber includes one or more of polypropylene fiber, polyester fiber, polyethylene fiber, and polyvinyl chloride fiber.

[0008] According to some embodiments of the denitrification catalyst described in this application, the amino acid includes arginine and / or histidine.

[0009] According to some embodiments of the denitrification catalyst described in this application, the clay mineral includes one or more of kaolinite, montmorillonite, illite, and talc.

[0010] According to some embodiments of the denitrification catalyst described in this application, the mass ratio of the activated carbon to the manganese dioxide is 1:(1.2-2.5).

[0011] According to some embodiments of the denitrification catalyst described in this application, the mass percentage of the plastic fiber in the denitrification catalyst is 8%-15%.

[0012] A second aspect of this application provides a method for preparing the denitrification catalyst described in the first aspect of this application, comprising the following steps:

[0013] (1) Activated carbon, manganese dioxide, arginine, phosphoric acid, phosphogypsum, alumina, clay minerals and plastic fibers are heated and mixed to obtain a mixture; (2) The mixture is freeze-dried and then calcined to obtain the denitrification catalyst.

[0014] According to some embodiments of the preparation method of the denitrification catalyst described in this application, the heating and mixing temperature is 110-120℃ and the time is 1-2h.

[0015] According to some embodiments of the preparation method of the denitrification catalyst described in this application, the freeze-drying temperature is -20°C to -40°C, and the time is 3-4 hours.

[0016] According to some embodiments of the preparation method of the denitrification catalyst described in this application, the calcination temperature is 600-800℃ and the time is 6-8h.

[0017] The beneficial effects of this application include: the denitrification catalyst described in this application is suitable for industrial mass production, has excellent low-temperature activity, stable structure, resistance to high temperature and aging, good dispersibility and sufficient active sites, strong resistance to poisoning, suitable for power plant flue gas rich in alkali metal particles and sulfides, high mechanical strength, strong plasticity and wear resistance, economical cost and solid waste resource utilization, high mass transfer efficiency, taking into account both adsorption and catalytic reactions, surface nanofilm can block water vapor from eroding active sites, the overall framework is a hydrophobic and stable structure, avoiding water vapor causing particle loosening and loss of active components, and performance does not decay under high humidity conditions. Detailed Implementation

[0018] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0019] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0020] This application provides a denitrification catalyst comprising the following raw materials in parts by weight: 10-15 parts activated carbon, 22-25 parts manganese dioxide, 12-15 parts amino acids, 3-8 parts phosphoric acid, 2-5 parts phosphogypsum, 5-8 parts alumina, 10-15 parts clay minerals, and 8-12 parts plastic fibers.

[0021] The denitrification catalyst described in this application is suitable for industrial mass production, exhibits excellent low-temperature activity, stable structure, resistance to high temperatures and aging, good dispersibility, sufficient active sites, strong resistance to poisoning, suitable for power plant flue gas rich in alkali metal particles and sulfides, high mechanical strength, strong plasticity and wear resistance, cost-effectiveness, utilization of solid waste resources, high mass transfer efficiency, and balances adsorption and catalytic reactions. The surface nanofilm blocks water vapor from eroding the active sites, and the overall framework is a hydrophobic and stable structure, avoiding the loosening of particles and loss of active components caused by water vapor. Its performance does not degrade under high humidity conditions.

[0022] In some embodiments of this application, the activated carbon includes one or more of coconut shell activated carbon, wood powder activated carbon, coal-based activated carbon, and bamboo-based activated carbon.

[0023] In some embodiments of this application, the plastic fiber includes one or more of polypropylene fiber, polyester fiber, polyethylene fiber and polyvinyl chloride fiber; the plastic fiber can form a pore to form a film, and the product is loose and porous, breathable and hydrophobic, which is suitable for the high water vapor conditions of gas turbines and coal-fired power plants.

[0024] In some embodiments of this application, the amino acids include arginine and / or histidine. High-temperature treatment of the amino acids can enhance the catalytic performance of manganese dioxide and significantly improve the catalyst's low-temperature denitrification activity.

[0025] In some embodiments of this application, the clay mineral includes one or more of kaolinite, montmorillonite, illite, and talc.

[0026] In some embodiments of this application, the mass ratio of activated carbon to manganese dioxide is 1:(1.2-2.5); for example, 1:1.2, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.5, etc.

[0027] In some embodiments of this application, the mass percentage of the plastic fiber in the denitrification catalyst is 8%-15%; for example, 8%, 9%, 10%, 12%, 15%, etc.

[0028] This application also provides a method for preparing the denitrification catalyst described in the first aspect of this application, comprising the following steps: (1) Activated carbon, manganese dioxide, arginine, phosphoric acid, phosphogypsum, alumina, clay minerals and plastic fibers are heated and mixed to obtain a mixture; (2) The mixture is freeze-dried and then calcined to obtain the denitrification catalyst.

[0029] In the preparation method of the denitrification catalyst described in this application, arginine exerts a chelating effect during the heating and mixing process. Combined with the interfacial activation effect of phosphoric acid, this allows active components such as manganese dioxide to be uniformly dispersed on the surface of various supports, preventing particle agglomeration from the source and ensuring the number and utilization rate of active sites. After mixing and calcination, alumina, clay minerals, and phosphogypsum form a stable inorganic framework. Combined with the overall dense structure, this makes the finished product wear-resistant, less prone to pulverization, suitable for industrial fixed-bed and other working conditions, and has a longer service life.

[0030] The denitrification catalyst preparation method described in this application achieves a pre-reaction of phosphoric acid and manganese species during the heating and mixing stage, initially forming a phosphate precursor; subsequent calcination further solidifies the catalyst to form a Mn-PO chemically bonded film, locking in the Mn-based active components, resisting high-temperature sintering and particle agglomeration, and extending its lifespan; the surface Brønsted acid sites (P-OH) are greatly increased, enhancing NH adsorption; and it resists PO4 poisoning. 3 -Preferentially binds to alkali metals (K) + / Na +Heavy metals and SO2 protect internal active sites; P has a higher electronegativity than Mn, which pulls electrons and increases the valence state of Mn (Mn 4+ (Increased), with stronger low-temperature redox activity; the nanofilm isolates dust and impurities, maintaining a high specific surface area and multiple active sites.

[0031] Amino acids and activated carbon powder, when heated to temperatures above 600℃, can promote the catalytic activity of manganese dioxide, increasing active sites, reactant adsorption, and low-temperature activity. The thermal decomposition of amino acids produces gas, increasing the mesoporous structure, specific surface area, and mass transfer efficiency. However, this process suffers from pore blockage and agglomeration, especially after absorbing large amounts of moisture, leading to component loss. It also exhibits poor sulfur resistance, is prone to poisoning and deactivation, and has relatively low mechanical strength, resulting in powder shedding. A membrane formed using polypropylene fibers is available, characterized by its fine, porous structure, breathability, and hydrophobicity, making it suitable for gas turbines and coal-fired power plants with moisture-rich flue gas. The addition of polypropylene fibers creates an overall hydrophobic membrane with unobstructed pores, preventing blockage and adapting to acidic power plant flue gas environments with high moisture content.

[0032] Phosphoric acid reacts with metal oxides such as phosphogypsum, kaolin, and alumina in the green body to form phosphate adhesives such as aluminum phosphate / calcium phosphate, which firmly bind aggregates such as gypsum powder and polypropylene fiber, improving the strength, mechanical strength, impact resistance, wear resistance, and crack prevention of the green body. After high-temperature firing, a stable phosphosilicate glass phase is formed, with overlapping layers forming a network skeleton, which acts as a skeleton reinforcement and bonding agent, improving powder formability, strengthening the structure, and making it water-resistant and durable. This prevents breakage and powder shedding during operation. After high-temperature hydration, a stable calcium-based crystalline phase is formed, filling the gaps in the skeleton, further densifying the overall structure, and improving the overall structural stability. The compound forms an inorganic rigid composite skeleton, reinforcing the single soft carbon skeleton and fundamentally solving the mechanical strength deficiency. High-temperature dehydration between phosphogypsum crystals forms a large number of micropores, and the combination of the three forms a multi-level channel with interconnected micropores, mesopores, and macropores. The pore size gradient increases, the diffusion resistance of flue gas and reactants is sharply reduced, and dust and macromolecular intermediates are less likely to be trapped. The inorganic carrier surface polarity differs from that of pure carbon, allowing for the modulation of surface functional groups and weakening the adsorption of carbon precursors. Simultaneously, it regulates the inner walls of the pores, inhibiting the adhesion and accumulation of salts such as ammonium bisulfate and ammonium chloride within the pores. The inorganic framework's thermal / hydrothermal stability is suitable for power plant flue gas; the pores do not shrink or collapse under high-temperature and humid conditions, maintaining their integrity over long-term use.

[0033] The denitrification catalyst described in this application has a simple process flow, no complicated intermediate steps, low operation difficulty, and is easy to scale up production; at the same time, it reuses industrial solid waste such as phosphogypsum and natural mineral raw materials, reducing raw material costs while ensuring performance, and has both resource utilization and environmental protection value.

[0034] In some embodiments of this application, the heating and mixing temperature is 110-120°C and the time is 1-2 hours, such as 1 hour, 1.5 hours, 2 hours, etc.

[0035] In some embodiments of this application, the freeze-drying temperature is -20°C to -40°C, such as -20°C, -25°C, -28°C, -30°C, -40°C, etc., and the time is 3-4 hours, such as 3 hours, 3.5 hours, 4 hours, etc. This application uses vacuum freeze-drying instead of conventional hot air drying, relying on ice crystal sublimation for dehydration. This avoids pore collapse and shrinkage due to surface tension, maintaining the multi-level porous structure and ensuring material mass transfer efficiency and adsorption capacity.

[0036] In some embodiments of this application, the calcination temperature is 600-800℃, such as 600℃, 650℃, 700℃, 730℃, 800℃, etc., and the time is 6-8h, such as 6h, 7h, 8h, etc. Phosphoric acid can react with metal oxides such as phosphogypsum, kaolin, and alumina in the green body to generate phosphate cementitious substances such as aluminum phosphate and calcium phosphate, which firmly bind aggregates such as gypsum and polypropylene fibers, improve the strength of the green body, and effectively prevent cracking; after high-temperature firing, a stable phosphosilicate glass phase is formed, which enhances the overall structural strength and makes it water-resistant and durable.

[0037] During the calcination process, the system releases water vapor and phosphorus pentoxide gas, forming interconnected micropores of 10-100μm. These micropores are fine and uniform in size, have high porosity, and good air permeability. Combined with the hydrophobic properties of polypropylene fibers, the pores can be prevented from being blocked by water vapor and dust under denitrification conditions, thus enabling the denitrification catalyst to have good adsorption performance and low-temperature catalytic activity.

[0038] By controlling the calcination temperature within this range, the decomposition of organic components, film solidification, and crystal phase regulation can be precisely completed. This fully leverages the modification effects of each component while avoiding the problems of high-temperature sintering and crystal phase deterioration, thus simultaneously enhancing the catalyst's low-temperature denitrification activity and anti-poisoning ability.

[0039] The technical solution of this application will be further described below with reference to specific embodiments. Example 1 A method for preparing a denitration catalyst includes the following steps: (1) Mix and grind 15 parts coconut shell activated carbon, 25 parts manganese dioxide, 15 parts arginine, 8 parts alumina, 15 parts kaolin and 5 parts phosphogypsum into powder to obtain primary slurry; (2) Heat the above primary slurry to 120°C, and add 8 parts of phosphoric acid and 13.5 parts of polypropylene fiber (the amount of polypropylene fiber added is 12% of the total mass of the denitrification catalyst) and stir for 1.5 h to obtain the mixture. (3) Pour the above mixture into a mold, cool and demold to obtain a billet, freeze dry the billet at -40℃ for 4 hours, and then calcine it at 600℃ for 6 hours (the heating rate during calcination is 10℃ / min) to obtain the denitrification catalyst.

[0040] Example 2 The only difference between the preparation method of the denitrification catalyst in Example 2 and that in Example 1 is that the amount of coconut shell activated carbon and polypropylene fiber added during the preparation of the denitrification catalyst in Example 2 is different from that in Example 1.

[0041] The specific operating steps include: (1) Mix and grind 10 parts of coconut shell activated carbon, 25 parts of manganese dioxide, 15 parts of arginine, 8 parts of alumina, 15 parts of kaolin and 5 parts of phosphogypsum into powder to obtain a primary slurry; the remaining operation steps are the same as in Example 1.

[0042] Example 3 The only difference between the preparation method of the denitrification catalyst in Example 3 and that in Example 1 is that the amount of coconut shell activated carbon and polypropylene fiber added in the preparation process of the denitrification catalyst in Example 3 is different from that in Example 1.

[0043] The specific operating steps include: (1) Mix and grind 20 parts of coconut shell activated carbon, 25 parts of manganese dioxide, 15 parts of arginine, 8 parts of alumina, 15 parts of kaolin and 5 parts of phosphogypsum into powder to obtain primary slurry; the remaining operation steps are the same as in Example 1.

[0044] Example 4 The only difference between the preparation method of the denitrification catalyst in Example 4 and that in Example 1 is that the amount of polypropylene fiber added during the preparation of the denitrification catalyst in Example 4 is different from that in Example 1.

[0045] The specific operating steps include: (1) Mix and grind 15 parts coconut shell activated carbon, 25 parts manganese dioxide, 15 parts arginine, 8 parts alumina, 15 parts kaolin and 5 parts phosphogypsum into powder to obtain primary slurry; (2) Heat the above primary slurry to 120°C, and add 8 parts of phosphoric acid and 16 parts of polypropylene fiber (the amount of polypropylene fiber added is 15% of the total mass of the denitrification catalyst) and stir for 1.5 h to obtain a mixture; the remaining operation steps are the same as in Example 1.

[0046] Example 5 The only difference between the preparation method of the denitrification catalyst in Example 5 and that in Example 1 is that the amount of polypropylene fiber added during the preparation of the denitrification catalyst in Example 5 is different from that in Example 1.

[0047] The specific operating steps include: (1) Mix and grind 15 parts coconut shell activated carbon, 25 parts manganese dioxide, 15 parts arginine, 8 parts alumina, 15 parts kaolin and 5 parts phosphogypsum into powder to obtain primary slurry; (2) Heat the above primary slurry to 120°C, and add 8 parts of phosphoric acid and 9 parts of polypropylene fiber (the amount of polypropylene fiber added is 9% of the total mass of the denitrification catalyst) and stir for 1.5 h to obtain the mixture; the remaining operation steps are the same as in Example 1.

[0048] Example 6 The only difference between the preparation method of the denitrification catalyst in Example 6 and that in Example 1 is that wood powder activated carbon is used instead of coconut shell activated carbon in the preparation process of the denitrification catalyst in Example 6.

[0049] Example 7 The only difference between the preparation method of the denitrification catalyst in Example 7 and that in Example 1 is that coal-based activated carbon is used instead of coconut shell activated carbon in the preparation process of the denitrification catalyst in Example 7.

[0050] Example 8 The only difference between the preparation method of the denitrification catalyst in Example 8 and that in Example 1 is that polyester fiber is used instead of polypropylene fiber in the preparation process of the denitrification catalyst in Example 8.

[0051] Example 9 The only difference between the preparation method of the denitrification catalyst in Example 9 and that in Example 1 is that polyethylene fiber is used instead of polypropylene fiber in the preparation process of the denitrification catalyst in Example 9.

[0052] Example 10 The only difference between the preparation method of the denitrification catalyst in Example 10 and that in Example 1 is that histidine is used instead of arginine in the preparation process of the denitrification catalyst in Example 10.

[0053] Example 11 The only difference between the preparation method of the denitrification catalyst in Example 11 and that in Example 1 is that lysine is used instead of arginine in the preparation process of the denitrification catalyst in Example 11.

[0054] Comparative Example 1 The only difference between the preparation method of the denitration catalyst in Comparative Example 1 and Example 1 is that arginine was not added during the preparation of the denitration catalyst in Comparative Example 1.

[0055] Performance study of the denitrification catalysts described in Examples 1-11 and Comparative Example 1 of this application The denitrification catalysts described in Examples 1-11 and Comparative Example 1 of this application were respectively loaded into the SCR steel reactor chamber (each device quantity was 200g), and 30mg / m³ was introduced through the inlet. 3 NO2 and 30mg / m 3A mixture of NH3 gas was used, and the catalyst reaction temperature was controlled at 120°C. A sensor was installed at the outlet to test and calculate the denitrification efficiency. The results are shown in Table 1. The catalyst reaction temperature of Example 1 was controlled, and the catalytic results at different temperatures are shown in Table 2.

[0056] Table 1

[0057] As can be seen from Table 1, comparing Examples 1-3, it can be seen that the catalytic performance of activated carbon dosage first increases and then decreases. An appropriate amount of carbon atoms can promote the catalytic activity of Mn atoms, while an excessive amount will lead to a decrease in the low-concentration denitrification efficiency because the adsorption of the denitrifying agent exceeds the catalytic reaction. Comparing Examples 1 and 4-5, it can be seen that the effect of plastic fiber dosage on overall performance first increases and then decreases with dosage. This is because an appropriate amount of plastic fiber creates pores, which increases the specific surface area and hydrophobic properties, thus increasing the denitrification efficiency. However, excessive dosage leads to a decrease in the proportion of effective catalytic sites.

[0058] Comparing Examples 1 and 6-7, it can be seen that coconut shell activated carbon has a greater promoting effect than medium activated carbon, which in turn has a greater effect than wood powder activated carbon. This is due to the effect of micropores and specific surface area.

[0059] Comparing Examples 1 and 8-9, it can be seen that polypropylene fiber is superior to polyethylene fiber, which is superior to polyurethane fiber in the system. This reflects the differences in pore-forming ability and stability among plastic fibers.

[0060] Comparing Example 1 and Examples 10-11, it can be seen that arginine is superior to histidine, which is superior to lysine, because the nitrogen atom content affects the activity of Mn atoms.

[0061] Table 2

[0062] As can be seen from Table 2, the denitrification catalyst described in this application has excellent low-temperature performance.

[0063] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.

Claims

1. A denitrification catalyst, characterized in that, The raw materials include the following parts by weight: 10-15 parts activated carbon, 22-25 parts manganese dioxide, 12-15 parts amino acids, 3-8 parts phosphoric acid, 2-5 parts phosphogypsum, 5-8 parts alumina, 10-15 parts clay minerals, and 8-12 parts plastic fibers.

2. The denitrification catalyst according to claim 1, characterized in that, The activated carbon includes one or more of coconut shell activated carbon, wood powder activated carbon, coal-based activated carbon, and bamboo-based activated carbon.

3. The denitrification catalyst according to claim 1, characterized in that, The plastic fibers include one or more of polypropylene fibers, polyester fibers, polyethylene fibers, and polyvinyl chloride fibers.

4. The denitrification catalyst according to claim 1, characterized in that, The amino acids include arginine and / or histidine.

5. The denitrification catalyst according to claim 1, characterized in that, The clay minerals include one or more of kaolinite, montmorillonite, illite, and talc.

6. The denitrification catalyst according to claim 1, characterized in that, The mass ratio of the activated carbon to the manganese dioxide is 1:(1.2-2.5). And / or, the mass percentage of the plastic fiber in the denitrification catalyst is 8%-15%.

7. The method for preparing the denitrification catalyst according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Activated carbon, manganese dioxide, arginine, phosphoric acid, phosphogypsum, alumina, clay minerals and plastic fibers are heated and mixed to obtain a mixture; (2) The mixture is freeze-dried and then calcined to obtain the denitrification catalyst.

8. The method for preparing the denitration catalyst according to claim 7, characterized in that, The heating and mixing temperature is 110-120℃, and the time is 1-2 hours.

9. The method for preparing the denitrification catalyst according to claim 7, characterized in that, The freeze-drying temperature is -20℃ to -40℃, and the time is 3-4 hours.

10. The method for preparing the denitrification catalyst according to claim 7, characterized in that, The calcination temperature is 600-800℃ and the time is 6-8h.